THE INFLUENCE OF PARENTS' EDUCATION LEVEL AND STUDENT LEARNING MOTIVATION ON STUDENT DISCIPLINE AT SD NEGERI KENDAWA 02, JATIBARANG DISTRICT, BREBES REGENCY - Farhan Sefudin Wahid; Alim Mutaqin (Sean Institute, 2022)
Discipline is important in conditioning a comfortable and peaceful learning environment in the school. This study aims to analyze the influence of parents' education levels and student learning motivation on the discipline of Kendawa 02 State Elementary School (SDN) students. The type of research used in this study is quantitative research with a descriptive approach. This study used an ex-post facto type with purposive sampling, which is a technique for determining techniques by determining certain criteria. Research data sources can be sourced from triangulation of data sources. Data collection techniques with observation and questionnaires. Data analysis techniques used with multiple regression tests. The results of the study obtained a t value calculating the level of education of parents < t table (-1.939 < 1.67203), which means that there is no influence of the variable level of parental education on the discipline of students of Public Elementary Schools Kendawa 02. The results of the value t calculate student learning motivation > t table (3.217 > 1.67203), which means that there is an influence of student learning motivation variables on the discipline of students of Public Elementary Schools Kendawa 02. The results of the regression test Y = (57,947) = -1,078 X1 + ,440 X2, which means that the variables of parental education level and student learning motivation simultaneously affect the discipline of students at Public Elementary Schools Kendawa 02, Jatibarang District, Brebes Regency.